Brand Image Produk Orisinil Menjadi Otentik Dalam Membangun Komunikasi Trend Bisnis - Badarudin Azarkasyi (Jurnal Komunikasi dan Budaya, 2020)
Business trends in the object of communication continue to develop with fierce pirated products (imitation) attacking the market then how business people can face and meet the wants and needs of the market. Formulate a strategy of how Product innovation does not neglect authentic touches but remains the main value of original products where business communication trends continue to evolve with the times, because products become the sensuality of personal communication shown to the public. On the problems and impacts on the background of this research problem using qualitative methods because the problems described are so complex, regarding quality, socially influential from these phenomena and strategy and control are needed in recognizing things that occur in the field. one of the strategies for business people continues to innovate products with an authentic touch. It is not only the originality of the product that must be maintained but how can realize the desires of consumers. Product brand image is inseparable from the characteristics, quality, authenticity, touch, needs and comfort that the product is built on, when mentioning a particular brand then we will know the identical product. communication business trends to innovate. the strategy is carried out for how to compete in the market without neglecting the communication of business trends, by reducing production costs through a combination of main and supporting materials from the surrounding environment, cultural touch, the main crops integrated while still building product confidence in consumers regarding product authenticity. As well as developing and building customer passion through authentic product innovation, so as not to release the identical, identical characteristics and characteristics of the product.